The different metabolomic profile of acupuncture stimulation in athletes after an 800-m running race and a training lesson - Guo, B.; Wu, Y.; WQang, X.; Zhao, Y.; Ma, H.; Jin, Y. (Medicina dello Sport, 2018)
BACKGROUND: The study is to investigate the different effects of traditional acupuncture on athletes who had done an 800-meter running race and exhaustive 3-hour drill by approach of NMR-based metabolomics. METHODS: Nineteen male athletes were randomly divided into two groups: training with acupuncture as a test group (A group) and training without acupuncture as a control group (R group). Both of the groups were loaded with 2 exercise programs: the single 800-meter running race program (program E) and the exhausting training class program (program T), 4 acupuncture points were selected: ST36, BL23, RN4 and BL40 on A group. The urine samples were collected at three different time points: before (E0, T0); 35 minutes after (E35, T35) exercise and 30 minutes after the different treatments (EA, ER; TA, TR). NMR measurements and Multivariate data analysis methods were applied. RESULTS: The metabolic cluster of EA and ER samples were moved closer towards E0, but the cluster of EA was not separated from ER. Samples TA and TR were separated in a PCA score plot. OPLS-DA score plots of TA samples moved closer towards T0 than TR. CONCLUSIONS: Based on proton NMR spectral analysis, acupuncture has different regulatory effects on different exercise programs. Acupuncture has no significant effect for the athletes with single 800-meter running race but has effect for the athletes with exhausting overload.